Perceptions of the rights and capabilities of people with intellectual disability in the United States. Issue 2 (19th October 2020) - McConkey, Roy; Slater, Paul; Smith, Ashlyn; Dubois, Lindsay; Shellard, Amy
Abstract: Background: The United States has yet to ratify the UN Convention on the Rights of Persons with Disabilities. The extent of public support in the United States for the rights of persons with intellectual disability is not known. Methods: Online public opinion polls were conducted nationally and in eight selected cities in 2017 and repeated in 2018 with 26, 876 respondents in total. Results: Support for rights was high: notably in accessing healthcare, schooling, playing sports and getting married. However, less support was evident for the rights of people who were perceived as less capable. Respondents with prior frequent personal contact and who had an engagement with Special Olympics were those most likely to support the rights and capabilities of persons with intellectual disability. Conclusions: Public support for the ratification of the UN Convention seems likely. Further longitudinal research could identify successful strategies for implementing the rights of disabled persons locally and nationally.